2016
DOI: 10.1021/acs.jpcc.6b04596
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Glass Transitions of Microphase Separed Binary Liquids Confined in MCM-41

Abstract: International audienceThe confinement of fluids in channels of nanometer size presents unprecedented opportunities to reveal emergent physicochemical properties that have no equivalent in the corresponding bulk system. We present an experimental study of fully miscible binary low-molecular weight liquids confined in nanopores. Under these conditions, the mixtures form a microphase-separated state with two regions of different compositions forming the core and the shell of a concentric tubular nanostructure. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…observed a higher tendency of ethanol to selectively adsorb on the pore walls of boron nitride, and showed that the ethanol/water partial demixing was relatively unaffected by the pore width (Figure b) . Similar microphase‐separated tubular structures seem to be a recurrent feature of binary liquid mixtures in mesopores, and are also supported by experimental evidences . For example, neutron diffraction experiments on MCM‐41 filled with a tert‐butanol‐toluene mixture evidenced inhomogeneous distribution of the components, suggesting that the pore surface is covered by tert‐butanol molecules, while toluene preferentially locates in the central region of the pore …”
Section: Empty Space Architecturesmentioning
confidence: 55%
See 1 more Smart Citation
“…observed a higher tendency of ethanol to selectively adsorb on the pore walls of boron nitride, and showed that the ethanol/water partial demixing was relatively unaffected by the pore width (Figure b) . Similar microphase‐separated tubular structures seem to be a recurrent feature of binary liquid mixtures in mesopores, and are also supported by experimental evidences . For example, neutron diffraction experiments on MCM‐41 filled with a tert‐butanol‐toluene mixture evidenced inhomogeneous distribution of the components, suggesting that the pore surface is covered by tert‐butanol molecules, while toluene preferentially locates in the central region of the pore …”
Section: Empty Space Architecturesmentioning
confidence: 55%
“…Recently, computational studies with slit‐pore models highlighted interesting organizational properties of confined fluids ,,,. According to Guo et al, an ethanol‐water mixture undergoes a partial demixing within the walls of an hydrophilic pore: while ethanol molecules tend to adsorb on surface silanols, water molecules preferentially interact among themselves, forming wires or clusters (Figure a) .…”
Section: Empty Space Architecturesmentioning
confidence: 99%
“…This direct experimental evidence of the core–shell organization represents a unique insight into allowing the investigation of the particular dynamical properties of these novel systems. Indeed, we evaluated the phase behavior and the glassy dynamics of TBA–TOL binary liquids confined in MCM-41 by the combination of neutron diffraction and differential scanning calorimetry (DSC) measurements in an attempt to examine the thermal behavior of this unusual phase in terms of density and heat capacity . Our studies revealed the coexistence of two different glass transitions, which suggests the existence of two spatially separated dynamics, likely attributed to the subcomponents of the microphase separated mixture.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these differences originate in the confinement of the molecules in nano or sub-nano structures. Sulfur allotropy 1 , change in electrochemical reactivity 2 , and ferroelectric properties of polymers in narrow nanotubes 3 , solar cell operations 4 , liquid crystals properties in microdroplets 5 , hydrogen atom transfer in micelles 6 , or glass transitions in mesoporous nanochannels 7 , are among recently described examples of such phenomena. Confinement, by influencing molecular vibrations 8 10 , can also lead to isotopic fractionation.…”
Section: Introductionmentioning
confidence: 99%